Follow-up case assessment form - Md Mustafa, Md Muziman Syah; Ahmad, Norsham (2020)
This follow-up case assessment form is developed as a tool to assess the ability of optometry students in analysing previous visit optometric record, and come out a proper plan and management with clinical justification for follow-up case in Primary Optometry Clinic I, II and III. It provides an assessment rubric to assist a clinical supervisor to grade the students' performance